STUDI PERBANDINGAN NILAI KUAT GESER BATU LEMPUNG BERDASARKAN KONDISI JENUH, KONDISI NATURAL, DAN KONDISI KERING FORMASI PALAU BALANG MENGGUNAKAN METODE DIREC SHEAR DI KALIMANTAN TIMUR - Irfan Irfan; Tommy Trides; Agus Winarno; Lucia Litha Respati; Shalaho Dina Devy (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2023)
: Claystone is a rock that has a denser structure with more mineral composition than siltstone. In addition, claystone can also be interpreted as a type of sedimentary rock that is clay or plastic, composed of hydrous aluminum silica (a clay mineral) whose grain size is fine and the claystone is often easily destroyed in a short time when it is exposed to the surface and interacts with water. From the test results it can also be obtained a comparison of rock strength values between location 1 and location 2 by correlating the results of testing the physical properties and mechanical properties of each location where for location 1 has a natural water content value of 17.38% and a saturated water content of 24.39% with the cohesion value of claystone under natural conditions is 0.209 MPa, saturated conditions are 0.2105 MPa and dry conditions are 0.2517 MPa. Then for location 2 it has a natural water content value of 22.87% and a saturated water content of 32.84% with a claystone cohesion value of natural conditions of 0.0923MPa, saturated conditions of 0.0377MPa and dry conditions of 0.2099 MPa. It can be concluded that the claystone location 1 has a smaller water content presentation than the claystone location 2. It can be concluded that the water contained in the claystone greatly influences the strength of the claystone in resisting the forces received to experience a shift and also water affects the attractive force between claystone particles which makes the strength of the rock weak.